Numerical solution for scattering of multilayer noble metal circular aperture arrays nanostructure. Issue 1 (July 2021) - Ji, Xiaowei; Zhou, Yu
Abstract: Due to its unique properties, metal-dielectric plasmonic structures have been widely applied in many fields, such as light absorption enhancement, surface enhanced spectrum, biosensor, and solar cell. We presented a numerical solution for light scattering from multilayer noble metal circular aperture arrays nanostructure. Using the generalized boundary conditions of surface impedance, the boundary value problem can be transformed into a set of integral equations about current density and magnetic density. Then utilizing the method of moments to solve these integral equations, more accurate reflected, transmitted, and absorbed power expressions can be obtained.